ACE inhibitors in arterial hypertension management: zofenopril – class-specific effects and extra benefits - V. S. Zadionchenko; T. V. Adasheva; M. V. Matsievich (Кардиоваскулярная терапия и профилактика)
The review is devoted to ACE inhibitor therapy in arterial hypertension (AH) management. The mechanisms of ACE inhibitors’ effects on oxidative stress, endothelial dysfunction, insulin and glucose metabolism are discussed. The data on pharmacological characteristics of zofenopril and its use in AH are presented.